Social interaction in urban areas: a case study of mixed and mono-ethnic neighbourhoods in Kuala Lumpur - Ahmad, Nobaya; Syed Abdul Rashid, Sharifah Norazizan (Universiti Putra Malaysia Press, 2003)
Malaysia has always been the focus of research towards understanding the social interaction and integration patterns of its multiethnic society. This study describes the social interaction patterns in residential neighbourhoods in Kuala Lumpur. The analysis was done to compare social interaction patterns between those who lived in mixed and mono-ethnic neighbourhoods, mainly Chinese or Malay. The findings suggested that there is a difference in the social interaction patterns where there were more socialisers, that is those who mixed with other ethnic groups, in mixed residential neighbourhoods compared to those who lived in mono-ethnic neighbourhoods.